Hierarchical Power Control With Interference Allowance for Uplink Transmission in Two-Tier Heterogeneous Networks - Kim, Dong In; Shin, Eun-Hee; Jin, Mi Seong (IEEE transactions on wireless communications, 2015)
In this paper, we propose a hierarchical power control (PC) algorithm with interference allowance (IA) in two-tier heterogeneous networks. Specifically, we consider a scenario where densely deployed femtocells exhibit on-off activity and a target macrocell base station (BS) is able to dynamically measure/estimate the sum interference from femtocell users in uplink transmission. In such a scenario, to mitigate the aggregate interference (AGGI) from active femtocells, the macrocell BS first decides macrocell user power based on the average uplink power budget, and then the IA per femtocell under hierarchical structure. Femtocell users then allocate their transmit power within the IA to suppress the cross-tier interference in heterogeneous networks. The PC algorithm should reflect the number of active femtocells to effectively control the AGGI, for which we propose a centralized sensing algorithm to estimate the number of active femtocells. Further, to track both the on-off activity and the random variations due to shadowing, we implement an iterative sensing algorithm which does not require cross-tier channel gains, suitable for wireless backhaul with higher latency and lower capacity. The iterative algorithm is shown to outperform the utility-based distributed power adaptation that requires the cross-tier channel gains, in terms of total cell throughput subject to the same outage rate.